Peningkatan Pemahaman Konsep Integral dengan Fash Method - Khoiruddin Matondang; Risna Mira Bella Saragih; Israq Maharani (Departement of Mathematics Education, 2023)
Integral is material that is difficult to understand for class XII SMA students. The long completion procedure saturates students and takes a long time. The solution to this problem is by applying the Fash Method learning. The purpose of this study was to determine the role of the integral fash method learning design in understanding mathematical concepts. The research method is descriptive research. The results of the research show that the fash method can motivate students to solve problems correctly and quickly.